Biodegradable high-adhesive antibacterial resin for aluminum-plastic composite and preparation method thereof
By using components such as PBAT, TPS, maleic anhydride graft and Fe-TCPP in the bonding resin of aluminum-plastic composite board, a biodegradable high-adhesion antibacterial resin is prepared, which solves the degradation and antibacteriality of traditional resins. The problem is that efficient aluminum-plastic composite bonding and environmentally friendly antibacterial effects have been achieved.
Patent Information
- Application Number
- CN202310160399.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-23
AI Technical Summary
The bonding resin of traditional aluminum-plastic composite boards cannot naturally degrade aerobicity, have low bond strength and are prone to bacterial growth, and antibacterial materials such as antibiotics and nano-silver ions can easily lead to strain resistance and human damage.
Polymers of poly-butylene adipate (PBAT), plasticized starch (TPS), maleic anhydride graft and tetracarboxyphenyl porphyrin iron (Fe-TCPP) are used to melt the components. The biodegradable high-adhesion antibacterial resin is mixed and heat bonded to the aluminum substrate.
The prepared resin material has high peel strength, strong antibacterial effect and high preparation efficiency. It can effectively bond aluminum-plastic composite boards and kill bacteria through the reactive oxygen species of Fe-TCPP under light, avoiding the side effects of antibiotics and metal ions. .
Smart Images

Figure CN116120874B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building decoration materials, in particular to a method for preparing a biodegradable high-adhesive antibacterial resin for aluminum-plastic composite. Background Art
[0002] Aluminum-plastic composite panels (hereinafter referred to as aluminum-plastic panels) are composite panels with aluminum materials bonded to one or both sides with resin. General resins are bonded through adhesive layer resins. The performance of the adhesive layer resin is closely related to the performance of the aluminum-plastic composite panel, and it is necessary to have extremely strong bonding strength. At the same time, aluminum-plastic composite panels, as decorative materials, often use maleic anhydride grafted polyethylene (PE-g-MAH), ethylene-vinyl acetate copolymer (EVA), etc. as the bonding layer. The surface is prone to breed a large number of bacteria and cannot be naturally degraded. Therefore, the development of biodegradable, highly adhesive antibacterial resins has significant application prospects and economic benefits.
[0003] At present, degradable materials are used to replace traditional resins as adhesive materials. For example, the hot melt adhesive made by the invention of publication number CN202210036968.4 can be completely degraded by aerobic composting. The adhesive materials prepared by the patent using polyester polyols, polycaprolactone, rosin glycerol ester modified terpene phenol resin, polybutylene adipate / terephthalate, maleic anhydride grafted white wax, etc. have good interfacial adhesion, but the base resin has a small molecular weight and low strength and is only suitable for the bonding of soft paper and other base materials. It has poor adhesion to hard materials such as aluminum-plastic composites. CN202111510466.2 modifies corn starch to obtain acid-modified TPS particles, and the acid-modified TPS particles are combined with EVA resin and tackifier to prepare TPS-based hot melt adhesive. This technology uses polyolefin petroleum resin in combination to improve the toughness of the base resin, but the general polyolefin resin EVA type hot melt adhesive cannot be naturally aerobically degraded, which greatly affects the biodegradability of the modified resin.
[0004] The biodegradability and antibacterial properties of resins are often a pair of contradictory issues. The application of biomass such as starch to resins makes the resins more typically affected by microbial bacteria. In order to improve the antibacterial properties of resins, antibiotics are usually loaded into the resin to exhibit bactericidal effects. For example, Zhang et al. [Ziwen Zhang, et al. (2021). "Synthesis and antibacterial activity of polymer-antibiotic conjugates incorporated into aresin-based dental adhesive". Biomaterials Science. 2021, 9: 2043-2052] prepared a monomer-antibiotic conjugate (MAC) containing a methacrylate monomer group and a PV part by nucleophilic substitution between 2-chloroethyl methacrylate (CEMA) and penicillin V potassium (PVK). As the biofilm acted for 24 to 72 hours, the number of bacteria was significantly reduced. However, the excessive use of antibiotics can easily cause bacteria to develop drug resistance, which poses a great challenge to the application of antibiotics in the medical field. CN114215972A reports a method for preparing a steel-plastic composite pressure pipe, which is used for pipeline transportation. The inner pipe includes an antibacterial layer of nano-silver particles, which can achieve a total antibacterial efficiency of 99% against staphylococci and Escherichia coli. However, the human body does not have an effective mechanism for excreting silver. Once silver accumulates in the bones and liver and causes poisoning, it cannot be detoxified. It will also complex with some groups or ions such as sulfonic acid groups, quaternary ammonium salt groups and hydroxides to produce precipitation, causing a certain degree of damage to the human internal organs.
[0005] Based on the above problems, traditional adhesive resins cannot be naturally degraded aerobically, degradable resins have low bonding strength and are prone to breeding bacteria, while antibiotics, nano-silver ions and other antibacterial materials are prone to causing drug resistance, human damage and many other effects. In addition, the adhesive layer resin acts on the bonding of general resin and aluminum, and should have strong body toughness while having good interface bonding. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and provide a biodegradable high-adhesive antibacterial resin for aluminum-plastic composite. The resin material produced by the method has the advantages of high peel strength, strong antibacterial effect and high preparation efficiency.
[0007] The specific steps of the technical solution are as follows:
[0008] A biodegradable high-adhesive antibacterial resin, wherein the resin substrate comprises the following components in parts by weight:
[0009] 60-80 parts of polybutylene terephthalate adipate (PBAT),
[0010] Plasticized starch (TPS) 20-40 parts,
[0011] 20-40 parts of maleic anhydride grafted compound,
[0012] 0.1-0.5 parts of tetracarboxyphenylporphyrin iron (Fe-TCPP),
[0013] Antioxidant 1010 0.2~0.4 parts.
[0014] Optionally, the maleic anhydride grafted product is maleic anhydride grafted PBAT (hereinafter referred to as: PBAT-g-MAH).
[0015] Optionally, the amylose content in the TPS is not less than 70%, and more preferably 70% to 80%.
[0016] Optionally, the TPS is obtained by plasticizing amylose using glycerol as a plasticizer.
[0017] Optionally, the melt index of the PBAT is 1.58-5g / 10min.
[0018] Optionally, the melting point of the PBAT is 130°C.
[0019] Another aspect of the present invention is to provide a method for preparing the above-mentioned biodegradable high-adhesive antibacterial resin, wherein PBAT, TPS, maleic anhydride grafted product, Fe-TCPP, and antioxidant 1010 are melt-blended to obtain the biodegradable high-adhesive antibacterial resin.
[0020] Optionally, the order of adding the above raw materials is PBAT, maleic anhydride grafted product and Fe-TCPP, TPS, and antioxidant 1010.
[0021] Alternatively, the maleic anhydride graft and Fe-TCPP are added simultaneously.
[0022] Another aspect of the present invention is to provide an application of the above-mentioned biodegradable high-adhesion antibacterial resin, wherein the resin is thermally bonded to an aluminum substrate to obtain a biodegradable high-adhesion antibacterial aluminum-plastic composite board.
[0023] Optionally, the thermal bonding time of the aluminum substrate and the plastic substrate is 5 min-10 min, the temperature is 150-160° C., and the pressure is 0.5 MPa-1 MPa.
[0024] Optionally, the aluminum substrate is subjected to surface degreasing treatment, such as acetone treatment, before thermal bonding, and then dried.
[0025] PBAT / TPS / maleic anhydride grafts have excellent interfacial polarity to bond with highly polar metal aluminum. At the same time, the strength and toughness of PBAT / TPS / maleic anhydride graft resins are also very high. When composited with relatively hard aluminum plastics, the resin can produce a large stress loss to significantly improve the bonding performance. On this basis, tetracarboxylphenylporphyrin iron (Fe-TCPP) is introduced into the PBAT / TPS / maleic anhydride graft resin system to enhance the antibacterial properties of the bonding resin. On the one hand, Fe-TCPP can bind O 2 Transformed into highly active 1 O 2 , thereby destroying the lipids of bacteria, etc., and playing a role in killing bacteria, with excellent antibacterial properties without side effects. On the other hand, it is difficult for ordinary inorganic powders to be dispersed in organic resins. The aggregation and agglomeration of inorganic powders not only fail to exert the functionality of inorganic powders, but also cause the performance of composite resins to decrease significantly. The powder in the present invention is also different from the grafting coupling of modified inorganic powders to produce a small amount of random surface organic means. The Fe-TCPP powder has symmetrical amino, hydroxyl, carboxyl and other structures, and has strong interactions with the hydroxyl and carboxyl groups of the matrix resin PBAT / TPS / maleic anhydride grafts. In addition, the benzene ring structure contained in Fe-TCPP can also react with the anhydride group on the maleic anhydride graft, stabilizing the phase state of the composite resin while being more conducive to the dispersion and antibacterial of Fe-TCPP in the matrix material. Therefore, the high-performance resin designed by PBAT, TPS, PBAT-g-MAH, and Fe-TCPP structures has excellent bonding, antibacterial and degradable properties.
[0026] Compared with the prior art, the present invention has the following advantages and significant progress:
[0027] (1) The present invention utilizes maleic anhydride grafts, such as PBAT-g-MAH, to adjust the compatibility between the two phases of the flexible structure PBAT and the strongly polar rigid structure plasticized starch, forming a local molecular chain penetration. At the same time, the Fe-TCPP powder in the present invention is also different from the conventional modified inorganic powder graft coupling to produce a small amount of random surface organic means, but utilizes the strong interaction between the symmetrical amino, hydroxyl, carboxyl, benzene ring of Fe-TCPP and the hydroxyl, carboxyl, anhydride group and other structures of the matrix resin to obtain a degradable high-adhesion antibacterial resin by melt blending. The adhesive resin prepared by the present invention has excellent interface polarity and toughness, and can produce great stress loss when bonded to a strongly polar aluminum plate to greatly improve the bonding performance. The photodynamic antibacterial agent Fe-TCPP can produce more strong interactions with the matrix and also ensure its dispersion effect and excellent antibacterial performance without side effects, avoiding the generation of drug-resistant bacteria caused by general antibiotics and the excessive use of metal ions causing ion deposition to damage human organs and tissues. At the same time, the matrix materials are all made of degradable resins, which will not cause environmental pollution and human harm. As a thermoplastic high-adhesion environmentally friendly modified resin, it has broad application prospects.
[0028] (2) The present invention adopts a melt blending method to prepare a biodegradable high-adhesive antibacterial resin, which has simple preparation process conditions, low production cost, easily available raw materials, degradable and pollution-free, uniform distribution of the internal structure of the resin, and stable product performance. It has the advantages of strong adhesion, degradability, and excellent antibacterial properties without side effects, which will become a preparation method of a biodegradable high-adhesive antibacterial resin for aluminum-plastic composites. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention is further described with reference to the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.
[0030] Figure 1 Schematic diagram of the design mechanism of the degradable high-adhesive antibacterial modified resin of the present invention;
[0031] Figure 2 The antibacterial performance of PBAT / TPS / PBAT-g-MAH / Fe-TCPP of Example 2 and PBAT / TPS / PBAT-g-MAH of Comparative Example 4 against Escherichia coli (E. coli) is compared, which are respectively an observation diagram of the inhibition zone and an electron microscope observation diagram of the hydrogel film surface. DETAILED DESCRIPTION
[0032] In order to make the present invention easier to understand, specific embodiments of the present invention will be further described below.
[0033] The preparation of the adhesive layer resin of the present invention is as follows:
[0034] PBAT is produced by BASF in Germany, with brand name C2332.
[0035] Preparation of TPS: 50 g corn starch and 15 g propylene glycol were mixed evenly with a high-speed pulverizer, placed at 60° C. for 3 h for pre-plasticization, and then melt-mixed at 140° C.-150° C. for 5 min with an open mill to prepare TPS.
[0036] PBAT-g-MAH: 50 g of PBAT was mixed with 1 g of maleic anhydride (MA) and 0.5 g of dicumyl peroxide (DCP) and then mixed in an internal mixer (140° C., 55 rpm, 10 min) to prepare PBAT-g-MAH.
[0037] Fe-TCPP: 8g Fe(NO 3 ) 3 9H 2 O and 11 g Na(OOCCH 3 )·3H 2 O was added into 9 mL of deionized water and stirred at room temperature until precipitation occurred. The filtered precipitate was washed with cold deionized water and dried in an oven at 100 °C for 12 h to obtain [Fe 3 O(OOCCH 3 ) 6 OH]·2H 2 O. Then 55 mg [Fe 3 O(OOCCH 3 ) 6 OH]·2H 2 O and 33 mg TCPP were added into a flask containing 50 mL DMF, 5 mL formic acid was added, and the mixture was stirred (500 rpm) at 80 °C for 24 h. The solution was centrifuged (10000 rpm) for 30 min and washed with DMF-centrifuged three times. The purple precipitate was dried and ground to obtain Fe-TCPP powder.
[0038] Comparative Example 1
[0039] TPS and antioxidant 1010 are pressed into a 1 mm thick plate at 150-160° C. using a flat vulcanizer. The obtained plate is thermally bonded to an aluminum substrate for 10-20 min at a temperature of 150-160° C. and a pressure of 0.5 MPa-1 MPa to obtain an aluminum-plastic composite plate.
[0040] Comparative Example 2
[0041] PBAT and antioxidant 1010 were melted at 150-160°C using an open mill, and then pressed into a 1mm thick plate at 150-160°C using a flat vulcanizer. The obtained plate was thermally bonded to an aluminum substrate for 10-20 minutes at a temperature of 150-160°C and a pressure of 0.5MPa-1MPa to obtain an aluminum-plastic composite plate.
[0042] Comparative Example 3
[0043] PBAT was melted at 150°C using an open mill, and TPS and antioxidant 1010 were added in turn and melted and blended using an open mill at 150°C-160°C, and then pressed into a 1mm thick plate using a flat vulcanizer at 150-160°C. The obtained plate was thermally bonded to an aluminum substrate for 10-20 minutes at a temperature of 150°C-160°C and a pressure of 0.5MPa-1MPa to obtain an aluminum-plastic composite plate.
[0044] Comparative Example 4
[0045] First, PBAT was melted at 150°C using an open mill, and then PBAT-g-MAH was added to melt and react for 5 minutes. Finally, TPS and antioxidant 1010 were added in sequence, and the mixture was continued for 5 minutes. Then, the mixture was pressed into a 1mm thick plate at 150-160°C using a flat vulcanizer. The obtained plate was thermally bonded to an aluminum substrate for 10-20 minutes at a temperature of 150-160°C and a pressure of 0.5MPa-1MPa to obtain an aluminum-plastic composite plate.
[0046] Examples 1-3
[0047] First, PBAT was melted at 150°C using an open mill, and then PBAT-g-MAH and Fe-TCPP were added to melt and react for 5 minutes. Finally, TPS and antioxidant 1010 were added in sequence, and the mixture was continued for 5 minutes. Then, the mixture was pressed into a 1mm thick plate at 150-160°C using a flat vulcanizer. The obtained plate was thermally bonded to an aluminum substrate for 10-20 minutes at a temperature of 150-160°C and a pressure of 0.5MPa-1MPa to obtain an aluminum-plastic composite plate.
[0048] The specific components of each comparative example and embodiment are shown in Table 1.
[0049] Antibacterial performance test:
[0050] Step (1): Weigh 1 g of peptone, 0.5 g of yeast powder, 1 g of NaCl and 1.5 g of agar powder respectively into a conical flask, mix well and seal the flask, and sterilize it in an autoclave twice, each time for 2 h.
[0051] Step (2): sterilize the culture dish with ultraviolet light for 20 minutes in a sterile fume hood, pour the liquid in step (1) into the culture dish while it is still hot, and cool and air-dry for 15 minutes to obtain a solid culture medium. Take 30 μm Escherichia coli liquid and spread it on the solid culture medium.
[0052] Step (3): Place a plastic sheet sample with a surface dryness and a diameter of 0.5 cm flat on the solid culture medium obtained in step (2), seal it with plastic wrap, and culture it in a shaking incubator at a constant temperature of 37° C. for 12 hours.
[0053] Step (4): Add 2.5 wt% glutaraldehyde to PBS at a pH of 7.4, and place the plastic disc cultured in the solid culture medium for 12 hours in step (4) therein to immerse and fix for 2 hours, thereby obtaining a treated plastic disc sample.
[0054] Step (5): freeze-dry for 24 h and spray with gold before conducting a scanning electron microscopy experiment.
[0055] Adhesion performance test:
[0056] The aluminum-plastic composite panel was cut into test samples with a length of 130 mm and a width of 25 mm. A universal tensile testing machine (MetS Industrial Systems China Co., Ltd., CMT2404) was used to perform a 180° peel test of the metal-plastic composite strip according to GB / T 8808-1998 standard, with a tensile rate of 300 mm / min. The test environment temperature was room temperature (25°C), and the test result was the average value obtained by testing 5 specimens.
[0057] The test data of the specific comparative examples and embodiments are shown in Table 1.
[0058] Table 1 Components, bonding properties and antibacterial properties of each comparative example and embodiment
[0059] like Figure 1 As shown, the aluminum-plastic composite board PBAT / TPS / PBAT-g-MAH mainly relies on TPS to provide strong polar surface adhesion, and the compatibility between the flexible structure PBAT and the rigid structure plasticized starch is adjusted by PBAT-g-MAH, and the local molecular chain penetrates to form a high-strength and tough matrix material. As shown in Table 1, after melt blending PBAT and TPS, Comparative Example 3 has stronger peel strength than Comparative Examples 1 and 2, but it belongs to cohesive failure. This is because the plastic forms a strong polar surface adhesion with the substrate surface, but the material is not enough to support the loss of large strain; while the peel strength of Example 2 is further improved, and it is an adhesive failure, because the effective molecular chain penetration of the matrix material PBAT / TPS / PBAT-g-MAH gives the matrix a stronger and tougher performance, which can produce greater stress loss to further improve the bonding performance.
[0060] The co-cultivation experiment of Examples 1 to 3 and Comparative Examples 1 to 4 and Escherichia coli (E. coli) was carried out. Figure 2As shown in the figure, compared with the PBAT / TPS / PBAT-g-MAH resin of Comparative Example 4, no bacteria were observed on the surface of the PBAT / TPS / PBAT-g-MAH / Fe-TCPP resin of Example 2, and the diameter of the inhibition zone was 1.1 mm, showing a strong antibacterial effect. This is because when Fe-TCPP was introduced into PBAT / TPS / PBAT-g-MAH, under light, PBAT / TPS / PBAT-g-MAH / Fe-TCPP fully converted O 2 Transformed into highly active 1 O 2 , thereby destroying the lipids of bacteria and killing E. coli; at the same time, Figure 1 As shown, the symmetrical amino, hydroxyl, carboxyl, benzene ring and other structures of Fe-TCPP have strong interactions with the hydroxyl, carboxyl and anhydride groups of the matrix resin, making the resin more antibacterial. The embodiment of the present invention mainly uses aluminum as the metal composite substrate, and the composite process provided can achieve good composite of aluminum and plastic substrate, and has degradable and antibacterial properties, solving the problems existing in the prior art.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A biodegradable high-adhesive antibacterial resin, characterized in that: The resin substrate comprises the following components in parts by weight: PBAT 60~80 copies, TPS 20~40 copies, 20-40 parts of maleic anhydride grafted compound, Fe-TCPP 0.1~0.5 parts, Antioxidant 1010 0.2~0.4 parts, in: Maleic anhydride grafted product is maleic anhydride grafted PBAT; Fe-TCPP is tetracarboxyphenylporphyrin iron; TPS is obtained by plasticizing amylose with glycerol as a plasticizer.
2. The biodegradable high-adhesive antibacterial resin according to claim 1, characterized in that: The amylose content in the TPS is not less than 70%.
3. The biodegradable high-adhesive antibacterial resin according to claim 1, characterized in that: The melt index of the PBAT is 1.58-5 g / 10 min.
4. The method for preparing a biodegradable high-adhesive antibacterial resin according to any one of claims 1 to 3, characterized in that: The plastic substrate is obtained by melt-blending PBAT, TPS, maleic anhydride grafted product, Fe-TCPP and antioxidant 1010.
5. The method for preparing the biodegradable high-adhesive antibacterial resin according to claim 4, characterized in that: The order of adding the raw materials is PBAT, maleic anhydride grafted product, Fe-TCPP, TPS, and antioxidant 1010.
6. The method for preparing the biodegradable high-adhesive antibacterial resin according to claim 4, characterized in that: The maleic anhydride graft and Fe-TCPP were added simultaneously.
7. Application of the biodegradable high-adhesive antibacterial resin according to any one of claims 1 to 3 or the biodegradable high-adhesive antibacterial resin obtained by the preparation method according to any one of claims 4 to 6 in the field of aluminum-plastic composite materials, characterized in that: The resin is thermally bonded to an aluminum substrate to obtain a biodegradable, highly adhesive, antibacterial aluminum-plastic composite panel.
8. The use according to claim 7, characterized in that The thermal bonding time between the aluminum substrate and the resin is 5 min-10 min, the temperature is 150-160° C., and the pressure is 0.5 MPa-1 MPa.
9. The use according to claim 7, characterized in that The aluminum substrate is subjected to surface degreasing treatment before thermal bonding.
Citation Information
Patent Citations
Steel-plastic composite pressure pipe
CN114215972A
Biodegradable TPS-based hot melt adhesive with high metal bonding strength as well as preparation and application of TPS-based hot melt adhesive
CN114381218A
A biodegradable hot melt adhesive for low-temperature paper bags and its preparation method
CN114395349B
Degradable antibacterial film and preparation method thereof
CN113667156A
Tissue bonding antibacterial hydrogel film and preparation method thereof
CN114920966A